Medical studies graduates on labour market (the example of Podlaskie Voivodeship) (Economic and Political Thought, 2014)
The article contains an in-depth analysis of medical graduates’ situationin the labour market., Podlaskie Voivodeship is used as an example. A surveywas conducted among 265 medical graduates, including 197 employed ones.